The new Strong's exhaustive concordance of the Bible : with main concordance, appendix to the main concordance, topical index to the Bible, dictionary of the Hebrew bible, dictionary of the Greek Testament - Strong, James, 1822-1894. (Nashville, Tenn. : T. Nelson Publishers, 1990)
Indexes the King James Bible.
Keywords: Bible -- Concordances, English; Hebrew language -- Dictionaries -- English; Bible -- Indexes; Greek language, Biblical -- Dictionaries -- English